2010
DOI: 10.1007/s12650-010-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a non-contact handling device using swirling flow with various gap height

Abstract: Vortex levitation can achieve non-contact handling by blowing air into a vortex cup through a tangential nozzle to generate a swirling flow. In this paper, we focused on the relationship between the sucking pressure and the flow dynamics when gap distance from the cup to a work piece changes. Then simultaneous measurement of a pressure and a flow field in the cup was performed. As a result, the mean pressure changes and the pressure fluctuation inside the cup enhances with increasing the gap height. Especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…The inner diameter of a tangential nozzle is d = 3.2 mm, and the height of the central area of the nozzle is 4 mm measured from the bottom of the cup. In order to observe pressure fluctuations, the workpiece was set at δ = 4 mm [13]. The diameter, D c , and height, H c , of the column are made dimensionless providing the variation as follow; H c /H = 0.34, 0.57, 0.90, D c /D = 0.42, 0.55, 0.63, 0.69, 0.76.…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The inner diameter of a tangential nozzle is d = 3.2 mm, and the height of the central area of the nozzle is 4 mm measured from the bottom of the cup. In order to observe pressure fluctuations, the workpiece was set at δ = 4 mm [13]. The diameter, D c , and height, H c , of the column are made dimensionless providing the variation as follow; H c /H = 0.34, 0.57, 0.90, D c /D = 0.42, 0.55, 0.63, 0.69, 0.76.…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…The cup was experimented under the Reynolds number (Re = VD/ν, here V is swirling velocity, ν is kinematic viscosity) of 58,000 based on the air flow velocity near the wall [12] [13]. In this study, V in , the flow speed at the nozzle, was set at 3.4 m/s to establish the flow similarity between the air-flow cup and the water-flow enlarged cup.…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…Because the structure of vortex gripper has the skirt but the cylinder does not have the skirt, the flow in the cylinder could not represent the flow in the vortex gripper. Iio et al 7 reported that simultaneous measurements of pressure and flow fields were performed to clarify the direct relationship between the lifting force and the swirling flow at various gap heights. In the experiment, water was used as a working fluid and its velocity was much smaller than the air velocity, but the viscosity was greater.…”
Section: School Of Mechanical Engineering Shanghai Jiao Tong Universmentioning
confidence: 99%
“…The pneumatic non-contact holder shown in Fig. 1 is liked in semiconductor manufacturing processes [3][4] because it has the following five advantages: (A) there is no chance of contamination or damage to a workpiece, and objects such as food can be transported under sanitary conditions, (B) it generates low heat or no magnetic field, (C) it is applicable to a variety of workpiece materials, (D) it does not require a control loop to obtain a stable state [5][6] , and (E) it is durable and requires no maintenance. There are several types of the holder, including Bernoulli and vortex holders.…”
Section: Introductionmentioning
confidence: 99%